Inflammatory myofibroblastic tumor of the gall bladder: a rare case report - Nangia, Anita; Sehgal, Shivali; Pujani, Mukta; Patiri, Karsing (Annals of Pathology and Laboratory Medicine, 2014)
Inflammatory myofibroblastic tumor (IMT) is a benign proliferation of myofibroblasts, which is prone to recurrence, persistent local growth as well as malignant transformation. The commonest site reported in the biliary tree is the extrahepatic bile duct. Gall bladder is a rare site for the development of an IMT. We report a case of an inflammatory myofibroblastic tumor of the gall bladder in an adult female with coextistent cholecystitis and cholelithiasis. It is important to acknowledge this entity since it can mimic malignancy.